Digital Support Systems for Vocational Education to Drive Sustainable Skill Development - Suherman, Suherman; Ismael, Ismael; Marlina, Leni; Hendry, Hendry (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This paper examines the role of Digital Support Systems in strengthening vocational education and accelerating sustainable skill development. The study highlights how integrated digital platforms, ranging from adaptive learning systems, virtual simulations, digital assessment tools, and learning analytics, enhance instructional quality, ensure competency alignment with industry demands, and improve learner engagement. The findings show that digital support systems enable more personalized learning paths, real-time performance monitoring, and greater accessibility for diverse learners. Moreover, these systems help vocational institutions respond quickly to evolving labor-market skills, reduce training gaps, and improve long-term workforce readiness. The paper concludes that adopting well-designed digital support systems is essential for building a resilient, future-oriented vocational education ecosystem capable of sustaining continuous skill development in the digital era.